POPULISME RELIGIUS: Promosi Image-Branding Majelis Shalawat dalam Industri Dakwah Kontemporer - Laili, Anisah Nur (Universitas Nurul Jadid, 2020)
This study aims to show majalis shalawat as a new religious market in contemporary Indonesia. Focusing on Syubbanul Muslimin and related to other majelis shalawat groups, this study analyzed kiai, gus, or habaib’s approaches in marketing and expanding the Islamic da'wah industry in urban and rural areas. The results showed that while most religious preachers use public speaking skills in religious markets, a leader of the Syubbanul Muslim and other majelis shalawat leaders are utilizing performance in improving their religious and market authority. Through this performance, they are actually deploying marketing strategies of promotion and image-branding to increase the number of followers.